Pengaruh Tingkat Pendidikan dan Pengeluaran Rumah Tangga terhadap Pendapatan Keluarga - Widyastuti, Lina; Mardiyanti, Rosa Amelia; Meyana, Sindy Putri; Banowati, Anysha; Wandansari, Lucky Titi; Andriani, Sandrina Febria (Universitas Muhammadiyah Surakarta, 2025)
This research aims to analyze the influence of education level and household expenditure on family income in Indonesia. A quantitative approach was used in this research with a multiple regression analysis method to examine the relationship between the independent variables (level of education and household expenditure) and the dependent variable (family income). The data used comes from a household survey with a sample of 300 families. The research results show that the level of education has a positive and significant influence on family income, which shows that the higher the education level of the head of the family, the greater the income generated. In contrast, household expenditure has a negative but significant relationship, meaning higher expenditure tends to hinder family income growth. The conclusion of this research is the importance of increasing access to education to increase family income and manage household expenses more efficiently.